Enterococcus faecalis promotes osteoclastogenesis and semaphorin 4D expression. Issue 7 (October 2015) - Wang, Shuai; Deng, Zuhui; Seneviratne, Chaminda J; Cheung, Gary SP; Jin, Lijian; Zhao, Baohong; Zhang, Chengfei
Enterococcus faecalis is considered a major bacterial pathogen implicated in endodontic infections and contributes considerably to periapical periodontitis. This study aimed to investigate the potential mechanisms by which E. faecalis accounts for the bone destruction in periapical periodontitis in vitro . Osteoclast precursor RAW264.7 cells were treated with E. faecalis ATCC 29212 and a wild strain of E. faecalis derived clinically from an infected root canal. The results showed that, to some extent, E. faecalis induced the RAW264.7 cells to form tartrate-resistant acid phosphatase (TRAP)-positive multinucleated osteoclast-like cells. This pathogen markedly stimulated RAW264.7 cells to express semaphorin 4D (Sema4D), which inhibits bone formation. Once RAW264.7 cells were primed by low-dose receptor activator of nuclear factor-kappa B ligand (RANKL), E. faecalis could significantly increase the production of TRAP-positive multinucleated cells and up-regulate the expression of osteoclast-specific markers, including NFATc1, TRAP and cathepsin K. Both p38 and ERK1/2 MAPK signaling pathways were activated by E. faecalis in RANKL-primed RAW264.7 cells, and meanwhile the expression of Sema4D was highly increased. In conclusion, E. faecalis may greatly contribute to the bone resorption in periapical periodontitis by promoting RANKL-dependent osteoclastogenesis and expression of Sema4D through activation of p38 and ERK1/2 MAPK signaling pathways.